2020
DOI: 10.1186/s13018-020-01806-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and treatment of “Non-dislocated hyperextension tibial plateau fracture”

Abstract: Background: To explore the epidemiological characteristics, clinical characteristics, treatment strategies, and clinical results of non-dislocated hyperextension tibial plateau fracture. Method: A total of 25 cases of non-dislocated hyperextension tibial plateau fracture patients were collected (12 males and 13 females), aged 27-79 years. Preoperative tibial plateau posterior slope angle was − 10~0°(average − 5.2°). Preoperative MRI showed 5 cases of MCL injury, 3 cases of PLC complex injury, and 2 cases of PL… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…However, dual incisions also require excessive stripping of soft tissue to expose the anterior compression fracture [9]. Therefore, a modi ed midline incision is recommended for fractures with little posterior displacement or tension failure, although this increases the frequency of soft tissue complications such as necrosis and infection [19,20]. Hence, anterolateral and posteromedial dual incisions are recommended when the posterior tibial cortex is displaced over 2 mm, the posterior hinge need to be reconstructed.…”
Section: Discussionmentioning
confidence: 99%
“…However, dual incisions also require excessive stripping of soft tissue to expose the anterior compression fracture [9]. Therefore, a modi ed midline incision is recommended for fractures with little posterior displacement or tension failure, although this increases the frequency of soft tissue complications such as necrosis and infection [19,20]. Hence, anterolateral and posteromedial dual incisions are recommended when the posterior tibial cortex is displaced over 2 mm, the posterior hinge need to be reconstructed.…”
Section: Discussionmentioning
confidence: 99%
“…This anatomically oriented classification including 2 columns and 4 quadrants can be easily remembered and used, and previous literature [ 13 ] showed good intraobserver and interobserver reliability, the mean Kappa value was 0.939 and 0.955, respectively. Second, it may facilitate hyperextensive TPF research because it contains all of the hyperextension TPF patterns reported in previous literature [ 2 , 3 , 6 , 10 , 23 ] and each fracture pattern only matches 1 certain type. Finally, it helps us choose suitable operative approaches for fracture fixation.…”
Section: Discussionmentioning
confidence: 99%
“…[ 8 ] Currently, because of a lack of a commonly accepted classification system based on anatomic fracture morphology, some confusing terms are used to indicate fracture subtypes caused by hyperextension injuries, such as “reverse Segond” fractures [ 9 ] and non-dislocated hyperextension TPFs. [ 10 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, a modi ed midline incision is recommended for fractures with little posterior displacement or tension failure, although this increases the frequency of soft tissue complications such as necrosis and infection [23,24]. Hence, anterolateral and posteromedial dual incisions are recommended when the posterior tibial cortex is displaced over 2 mm, the posterior hinge need to be reconstructed.…”
Section: Clinical Outcomesmentioning
confidence: 99%